Activation dynamics of antigen presenting cells in vivo against Mycobacterium bovis BCG in different immunized route - Zhengzhong Xu; Xin Li; Aihong Xia; Zhifang Zhang; Jiaxu Wan; Yan Gao; Chuang Meng; Xiang Chen; Xin-an Jiao (BMC Immunology, 2023)
Abstract Background Control of Tuberculosis (TB) infection is mainly the result of productive teamwork between T-cell populations and antigen presenting cells (APCs). However, APCs activation at the site of initiating cellular immune response during BCG early infection is not completely understood. Methods In this study, we injected C57BL/6 mice in intravenous (i.v) or subcutaneous (s.c) route, then splenic or inguinal lymph node (LN) DCs and MΦs were sorted, and mycobacteria uptake, cytokine production, antigen presentation activity, and cell phenotype were investigated and compared, respectively. Results Ag85A-specific T-cell immune response began at 6 days post BCG infection, when BCG was delivered in s.c route, Th17 immune response could be induced in inguinal LN. BCG could induce high level of activation phenotype in inguinal LN MΦs, while the MHC II presentation of mycobacteria-derived peptides by DCs was more efficient than MΦs. Conclusions The results showed that BCG immunized route can decide the main tissue of T-cell immune response. Compared with s.c injected route, APCs undergo more rapid cell activation in spleen post BCG i.v infection.